State Intervention Behind The Election of The Grand Imam of Al-Azhar: A Critical Discourse Analysis of The Film Boy from Heaven - Ismail Fahmi; Muhammad Faisol (Universitas Ahmad Dahlan, 2025)
This study aims to reveal the forms of Egyptian state intervention in the religious institution of Al-Azhar, as represented in the film Boy from Heaven. The film portrays the state intelligence apparatus's involvement in the process of electing the Grand Imam of Al-Azhar as part of a political project aimed at controlling religious legitimacy. This study uses Norman Fairclough's Critical Discourse Analysis approach, which includes three dimensions: text, discursive practice, and socio-cultural practice. The results of the study found eight forms of intervention, including the production of dominant narratives, recruitment of informants, coalitions with extremist groups, intimidation, threats, legitimating narratives through murder, periodic monitoring, delegitimation politics, and arrests of candidates. These representations show the state's authoritarianism to obtain political interests and how language and narrative are used as tools of hegemony. These findings reflect the dynamics of political-religious relations in Egypt and expand the application of the critical discourse approach in studying language through fictional media.